2016
DOI: 10.2147/ott.s110558
|View full text |Cite
|
Sign up to set email alerts
|

Cervical nodal necrosis is an independent survival predictor in nasopharyngeal carcinoma: an observational cohort study

Abstract: PurposeMost nasopharyngeal carcinoma (NPC) patients present with locoregionally advanced disease at the time of diagnosis; however, there is a lack of consensus on specific prognostic factors potentially improving overall survival, especially in late-stage disease. Herein, we conducted a retrospective study to evaluate various potential prognostic factors in order to provide useful information for clinical treatment of T3/T4-stage NPC.Patients and methodsA total of 189 previously untreated NPC patients were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Patients with nodal necrosis had worse OS and DMFS (OS, 78.8% vs. 91.8%; DMFS, 78.4% vs. 91.6%, both p < 0.001); the author proposed that patients with nodal necrosis should be upstaged by one level in their respective N‐category. Other studies showed similar findings, with the hazard ratio for OS ranging from 1.36 to 2.15 in the presence of nodal necrosis 89‐93 . The prognosis and pattern of failure were found to be affected by the degree of necrosis 93 …”
Section: Nodal Features That Influence Prognosissupporting
confidence: 55%
“…Patients with nodal necrosis had worse OS and DMFS (OS, 78.8% vs. 91.8%; DMFS, 78.4% vs. 91.6%, both p < 0.001); the author proposed that patients with nodal necrosis should be upstaged by one level in their respective N‐category. Other studies showed similar findings, with the hazard ratio for OS ranging from 1.36 to 2.15 in the presence of nodal necrosis 89‐93 . The prognosis and pattern of failure were found to be affected by the degree of necrosis 93 …”
Section: Nodal Features That Influence Prognosissupporting
confidence: 55%
“…It is reported that the many factors are involved in the development of NPC, including exposure to chemical carcinogens, latent Epstein‐Barr virus infection, genetic predisposition, and epigenetic variations . Moreover, previous evidence shows that NPC is difficult to be diagnosed because of nonspecific symptoms including trismus, otitis media, nasal regurgitation, hearing loss, pain, and cranial nerve pulses; thus most patients have regional node metastasis when diagnosed . Although, in recent years, there have been achievements in diagnostic methods, low overall survival rates still accompanied due to high incidence of local recurrence and distant metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…2 Moreover, previous evidence shows that NPC is difficult to be diagnosed because of nonspecific symptoms including trismus, otitis media, nasal regurgitation, hearing loss, pain, and cranial nerve pulses; thus most patients have regional node metastasis when diagnosed. 3 Although, in recent years, there have been achievements in diagnostic methods, low overall survival rates still accompanied due to high incidence of local recurrence and distant metastasis. 4 Therefore, it is necessary for us to figure out the molecular mechanism underlying NPC for future treatment.…”
mentioning
confidence: 99%
“…[ 34 36 ] However, the cut-off values of the maximal axial dimension of the lymph node varied in these studies, and they were partly based on evidence from the seventh edition system. [ 30 , 31 , 34 38 ] Therefore, improvements to the N classification system require further investigation, including unified criteria for measuring nodal size.…”
Section: Discussionmentioning
confidence: 99%